PENGARUH KOMITMEN ORGANISASI, MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI KECAMATAN LENTENG KABUPATEN SUMENEP - jurnalmap map; Dororul AÔÇÖla Masyhurad; Chamariyah ÔÇì; Subijanto ÔÇì (MAP (Jurnal Manajemen dan Administrasi Publik), 2019)
ABSTRACT The purpose of this study is to study whether organizational commitment, motivation, and good work coordination simultaneously influence significantly on the performance of employees of Lenteng Sub-District, Sumenep Regency, and to find out variables related to organizational commitment, motivation and significant partial cooperation with Lenteng District employee support. Sumenep Regency. This research was conducted at the Lenteng District Office in Sumenep Regency with a total sample of 34 people. The type of research used in this study is explanatory research (explanatory research). The main research used is quantitative and equipped with descriptive. The results of the study showed that simultaneously, organizational commitment, motivation and work discipline were significant towards the performance of employees of the Lenteng District of Sumenep Regency. Partially, organizational commitment, motivation and work discipline are significant to the performance of employees of the Lenteng District of Sumenep Regency. Motivation has a dominant and significant influence on the performance of employees of Lenteng District, Sumenep Regency. Keywords: organizational commitment, motivation, work discipline, employee performance